Dyadic analysis of very old parents' and their children's interdependence and self-perceptions of aging. (January 2023) - Kim, Yijung K.; Kim, Kyungmin; Jopp, Daniela S.; Boerner, Kathrin
The number of families with very old members is growing, and their intergenerational experiences may have significant ramifications for how the family members view their own aging. Using 114 dyads of very old parents ( M age = 93.31) and their "old" children ( M age = 67.78), we investigated whether one's own (i.e., parents or children) and each other's (i.e., children or parents) reports of relationship quality, care experiences, and health were associated with self-perceptions of aging. At the bivariate level, parents' ratings of relationship quality and care experiences were related to some of the children's health indicators, and vice versa. Very old parents reported less positive self-perceptions of aging than their children, and there was no within-dyad similarity in self-perceptions of aging. Individuals' own health indicators (i.e., functional limitations, chronic conditions, and depressive symptoms) were associated with their self-perceptions of aging. For parents, their own report of more depressive symptoms was associated with less positive self-perceptions of aging. For children, their own report of more depressive symptoms as well as functional limitations was associated with less positive self-perceptions of aging. Care experiences demonstrated a partner effect for parents, such that children's report of more caregiving burden was associated with parents' less positive self-perceptions of aging. The findings provide initial evidence to assess the interdependence of self-perceptions of aging within parent-child ties in very late life. Despite the generational difference in the level of self-perceptions of aging, various facets of the informal care context may contribute to how older individuals view their own aging trajectory.